Topological response of the anomalous Hall effect in MnBi2Te4 due to magnetic canting - S.-K. Bac (npj Quantum Materials, 2022)
Abstract Three-dimensional (3D) compensated MnBi2Te4 is antiferromagnetic, but undergoes a spin-flop transition at intermediate fields, resulting in a canted phase before saturation. In this work, we experimentally show that the anomalous Hall effect (AHE) in MnBi2Te4 originates from a topological response that is sensitive to the perpendicular magnetic moment and to its canting angle. Synthesis by molecular beam epitaxy allows us to obtain a large-area quasi-3D 24-layer MnBi2Te4 with near-perfect compensation that hosts the phase diagram observed in bulk which we utilize to probe the AHE. This AHE is seen to exhibit an antiferromagnetic response at low magnetic fields, and a clear evolution at intermediate fields through surface and bulk spin-flop transitions into saturation. Throughout this evolution, the AHE is super-linear versus magnetization rather than the expected linear relationship. We reveal that this discrepancy is related to the canting angle, consistent with the symmetry of the crystal. Our findings bring to light a topological anomalous Hall response that can be found in non-collinear ferromagnetic, and antiferromagnetic phases.